Change in stroke incidence, mortality, case-fatality, severity, and risk factors in Oxfordshire, UK from 1981 to 2004 (Oxford Vascular Study). - Rothwell, P; Coull, A; Giles, M; Howard, S; Silver, L; Bull, L; Gutnikov, SA; Edwards, P; Mant, D; Sackley, C; Farmer, A; Sandercock, P; et al. (2004)
BACKGROUND: The incidence of stroke is predicted to rise because of the rapidly ageing population. However, over the past two decades, findings of randomised trials have identified several interventions that are effective in prevention of stroke. Reliable data on time-trends in stroke incidence, major risk factors, and use of preventive treatments in an ageing population are required to ascertain whether implementation of preventive strategies can offset the predicted rise in stroke incidence. We aimed to obtain these data. METHODS: We ascertained changes in incidence of transient ischaemic attack and stroke, risk factors, and premorbid use of preventive treatments from 1981-84 (Oxford Community Stroke Project; OCSP) to 2002-04 (Oxford Vascular Study; OXVASC). FINDINGS: Of 476 patients with transient ischaemic attacks or strokes in OXVASC, 262 strokes and 93 transient ischaemic attacks were incident events. Despite more complete case-ascertainment than in OCSP, age-adjusted and sex-adjusted incidence of first-ever stroke fell by 29% (relative incidence 0.71, 95% CI 0.61-0.83, p=0.0002). Incidence declined by more than 50% for primary intracerebral haemorrhage (0.47, 0.27-0.83, p=0.01) but was unchanged for subarachnoid haemorrhage (0.83, 0.44-1.57, p=0.57). Thus, although 28% more incident strokes (366 vs 286) were expected in OXVASC due to demographic change alone (33% increase in those aged 75 or older), the observed number fell (262 vs 286). Major reductions were recorded in mortality rates for incident stroke (0.63, 0.44-0.90, p=0.02) and in incidence of disabling or fatal stroke (0.60, 0.50-0.73, p<0.0001), but no change was seen in case-fatality due to incident stroke (17.2% vs 17.8%; age and sex adjusted relative risk 0.85, 95% CI 0.57-1.28, p=0.45). Comparison of premorbid risk factors revealed substantial reductions in the proportion of smokers, mean total cholesterol, and mean systolic and diastolic blood pressures and major increases in premorbid treatment with antiplatelet, lipid-lowering, and blood pressure lowering drugs (all p<0.0001). INTERPRETATION: The age-specific incidence of major stroke in Oxfordshire has fallen by 40% over the past 20 years in association with increased use of preventive treatments and major reductions in premorbid risk factors.